An analysis of Section 11 of the Constitution and 'Stransham-Ford v Minister of Justice': are people permitted to waive the right to life? - Mlotshwa, Vanessa (Department of Public Law, 2024)
Thousands of people around the world seek active euthanasia as a medical means to the alleviation of their incurable pain. This highly contentious medical procedure is not available to South Africans. This thesis explores the High Court Judgment of Stransham-Ford v Minister of Justice, the first case legalising both passive and active euthanasia in South Africa; and the subsequent overturning of that judgment by the Supreme Court of Appeal. This thesis assesses applicable case law and engages the relevant secondary sources of literature to determine if there is a pathway for the legalisation of active euthanasia in South Africa. Furthermore, this thesis conducts a section 36 general limitations examination of the key constitutional rights that govern this matter, including section 11 (right to life), section 10 (right to dignity) and section 12(2) (right to informed consent). Thereafter this thesis reviews the foreign law of jurisdictions where euthanasia has been legalised. This includes an evaluation of Canadian case law which utilised the Canadian Charter of Rights and Freedoms to legalise euthanasia. This Charter was one of the inspirations for the South African Constitution. Finally, the thesis makes provision for medical professionals to object to performing euthanasia based on conscience or religion.